3D Printing of Polymer-Derived Graphene/SiCp/SiC Composite by Direct Ink Writing - Hongjun Liu; Yajun Li; Run Tang; Yamin Li (Crystals)
The direct ink writing (DIW) process has been successfully used to prepare SiC-based composites from preceramic polymers due to the porous light weight, lower sintering temperature, and tailored design. However, it still presents challenges in improving the mechanical properties of composites and endowing them with multifunctionality. In this study, we present a 3D-printing strategy for preparing a graphene/SiCp/SiC composite using the DIW process. A polycarbosilane (PCS)-based slurry containing graphene/SiCp composite powder was developed and 3D-printed into scaffolds with a lattice structure, which were then pyrolyzed at 1500 °C to obtain a graphene/SiCp/SiC composite. The weight loss, viscosity, and printability of the graphene/SiCp/PCS slurry were evaluated, and it was determined that the slurry after 4 h of magnetic stirring was suitable for the DIW process. When heat-treated at above 800 °C in an N2 atmosphere, PCS was first reacted with SiCxOy, which was further transformed into β-SiC and pyrocarbon. The 3D-printed lattice structure achieved porosity and low density, while the SiCp reduced defects caused by large shrinkage during pyrolysis of PCS. Meanwhile, GNPs provided the composites with better conductivity and lower density. The density was as low as 1.08 g/cm3, the conductivity reached 670 S·m−1, and the compressive strength was 4.3 MPa. Thus, a lightweight and porous SiC-based composite with high conductivity and strength can be prepared.